Chronology and documentary handbook of the State of New Mexico - Vexler, Robert I. (Dobbs Ferry, N.Y. : Oceana Publications, 1978)
A chronology of historical events in the state of New Mexico with selected documents, biographical outlines of politicians and prominent personalities, and a name index.
Cover title: New Mexico, a chronology & documentary handbook.
Includes index.
Bibliography: p. 145.
Keywords: New Mexico -- History -- Chronology; New Mexico -- Biography; New Mexico -- History -- Sources; New Mexico -- History